Elaboração, aplicação e avaliação de uma programação para o ensino informatizado, a futuros professores, de relações condicionais envolvidas na leitura inicial/rudimentar, por meio do procedimento de MTS - Penariol, Camila Politi (2011)
According to stimulus equivalence paradigm, reading consists of relations among different classes of stimuli, in which some of these stimuli are directly taught and others are derived from direct teaching. The procedure called Matching-To-Sample (or MTS) is usually used in the construction of methods for teaching academic repertoires such as reading, to diverse populations, based on the stimulus equivalence paradigm. With advances in computer, programs were developed for the implementation of MTS tasks using the computer. These programs are widely used in researches, however, broadening the potential of this technology depends on its use in applied settings such as schools. In this case, an existing question refers to which repertoires are necessary for an individual with no formal training in research and without knowledge about the theoretical and methodological assumptions of the area of Behavior Analysis to implement successfully matching-to-sample procedures to teach children in applied settings, such as school. Thus, from a systematic replication of the study in progress, developed by Oliveira (2010), this study aimed to program and evaluates a teaching program of undergraduate students for the implementation of the computerized procedure Matching-To-Sample through two studies, described below. In Study 1, participants were four undergraduate students. Initially, a set of three stimuli was used to teach participants to: (1) program AC (dictated word-printed word) training; (2) implement AC training; and (3) analyze data performance of the learner. The procedure consisted of teaching demonstration followed by instruction to repeat the demonstration. Verbal praise following correct answers and incorrect answers end of the trial and replay of the demonstration. The performance criterion was 100% correct responses. Later, generalization tests were conducted with three new sets of stimuli. Consequences for performance differentials were removed and the performance criterion was 100% correct answers. Study 2 involving three new participants and modification of the teaching procedure. It was conducted in a manner analogous to that described in Study 1, except as provided below. Before the teaching sessions, sessions were held to baseline: (1) program AC training; (2) implement AC training; and (3) analyze data performance of the learner. The sessions were performed as described in Study 1, except that differential consequences for performance have been removed. After, teaching sessions were introduced with a demonstration followed by instruction to repeat the demonstration. Correct answers were followed by verbal praise and incorrect answers within the "Retry" and a new opportunity to respond, unlike Study 1. Criterion to finish sessions was 100% of correct responses. Next, participants were presented with generalization tests. During testing sessions, there were no scheduled consequences for participant responses. Criterion to finish the session was 100% of correct responses. According to the results of Studies 1 and 2, all participants met criterion in the three phases of training and showed generalization of repertoire to news sets of stimuli. Results showed that the procedure may be used as a sound basis for the development of a program for teachers. The results suggest that the procedure may be efficient to teach teachers to implement Matching-To-Sample procedures, extending the technology derived from Behavior Analysis Applied to applied settings, 4 such as classrooms and schools. Furthermore, this study could leverage future research with similar goals.